Emotional Regulation Training Improves Psychological Well-Being and Marital Happiness Among Young Married Couples - Okky Naomi Sahupala; Masnaeni Ahmad; Muhammad Jawneh (Bulletin of Counseling and Psychotherapy, 2026)
This randomized controlled trial evaluated the efficacy of a culturally-adapted emotion regulation intervention for young married couples. Grounded in Gross's process model and integrated with local cultural values, the intervention aimed to enhance psychological well-being and marital happiness. Sixty participants (30 couples) in West Sulawesi were randomly assigned to an 8-session intervention group (n=30) or an active control group receiving standard health education (n=30). Pre- and post-test assessments using the Emotion Regulation Questionnaire, Ryff's Psychological Well-Being Scale, and the Marital Happiness Scale revealed that the intervention group demonstrated significantly greater improvements in emotion regulation (F(1,58)=25.34, p<.001, ηp²=.30), psychological well-being (F(1,58)=18.92, p<.001, ηp²=.25), and marital happiness (F(1,58)=22.15, p<.001, ηp²=.28) compared to controls. Qualitative findings further revealed enhanced emotional awareness and improved dyadic communication. Results support the intervention as an effective clinical-positive psychology model for enhancing mental health and relational well-being in young couples, with significant implications for culturally-informed public mental health initiatives in Indonesia.